Social Media and War on Gaza: A Battle on Virtual Space to Galvanise Support and Falsify Israel Story - Hatem El Zein; Ali Abusalem (Athens Journal of Mass Media and Communications, 2015)
The development in the communication network technology has changed drastically the narration of the prolonged war in the Middle East. It has provided the militant organisations, their supporters and their enemies another platform to ignite their war on the cyberspace. Taking the rise of notorious organisations, such “The Islamic State in Iraq and Syria [or the Levant]” (ISIS or ISIL), and their online broadcasting of statements, horrified images and videos alongside a machine of supporters to recruit new fighters, this example provides an insight on the impact of social media to militant organisations. The recent fifty days of Israel war on Gaza Strip, which named by Israel “Protective Edge Operation”, emphasised the ken about the role of social media during the conflict. It has become a savvy way to win the war, because the level of success is measured by wining the hearts and minds of people, and consequently to demoralise the spirit of the enemy. This paper is an endeavour to review the Palestinian's performance on social media during the war on Gaza. It intends to show the media tactics of the Palestinian militant organisations in Gaza and Gaza’s sympathisers. In the context, the paper will show also the Israeli utilisation of social media to legalise bombing on Gaza.